Patrimônio cultural, memória e identidade : um estudo etnográfico sobre processos de interação de atores humanos com monumentos cívicos - Oliveira, Lenora Azevedo de (2018)
This work is a study of human interaction with civic monuments examining the constellation of cultural heritage, memory and identity. Civic monuments are built with the purpose of establishing and maintaining values considered central to a social group, usually linked to identity and memory, serving as material support for existing traditions or for the construction of new traditions. The ethnographic method’s objective is to understand contemporary cultural practices and to determine to what extent these practices have changed since the construction of the monument, with or without the establishment of other and different practices. Three monuments were chosen for this analysis: the Julio de Castilhos Monument in Porto Alegre, Brazil, the war memorial monument at North Bondi and the Anzac Memorial Hyde Park, both in the city of Sydney, Australia. Research has shown that social interactions with monuments can contribute to a feeling of belonging to a social group and the interaction with cultural heritage could build and maintain memory and identity. Research on social practices with the monuments indicates that this may or may not contribute to the feeling of belonging to a social group. Cultural heritage, tangible (monuments) and intangible (rituals), are examined specifically in the way memory and identity are created and maintained. The act of remembering is directly tied to social practices and the more emotions experienced in the social practice the greater the capacity of the individual to remember. Monuments can be as powerful a “memory support” (NORA, 1993) as they can be a “historical support”. They are memory support when associated with living memory. If there is no kind of memory associated with them, monuments can be redefined and social practices will be disconnected from the monument’s original function.